AN INVESTIGATION OF EXPERIMENTAL PARAMETERS REQUIRED TO STUDY HYDROCARBON PHASE BEHAVIOR UNDER CONSTANT VOLUME AND CONSTANT COMPOSITION CONDITIONS - Cholkar, Abhijeet (My University, 2016)
Accurate fluid phase behavior evaluation is essential for reservoir engineers to predict the type of reservoir, oil and gas in place, and develop proper production strategies. The change in phase behavior and phase equilibrium are key to understand the reservoir condition and estimate production from a particular formation. In shale reservoirs, hydrocarbon phase behavior in nanopores can be affected by various factors such as pore proximity and pore size distribution. In many shale and tight oil and gas reservoirs, pore sizes are in the ranges of nanometers. Various simulation models are seen in literature attempting to predict phase behavior under confinement but there is no good reference of experimental results for verification. Our research team is trying to conduct phase behavior tests for single, binary, and multi-component hydrocarbon mixtures under confinement to validate and test the various simulation models. Since that’s not an easy endeavor, each of us in the research team has taken on one of the challenging tasks to accomplish the goal. My particular goal is to examine the feasibility of a new experimental procedure for detecting the edge of the phase envelope. The new experimental approach for detecting the phase envelope was examined through numerical simulation of binary hydrocarbon mixtures in bulk since these bulk simulation numbers have been verified experimentally in the past. The binary hydrocarbon mixtures we examined were Ethane with Propane, Pentane, Heptane and Hexane with 50-50 mole percentage. As per the experimental feasibility in the laboratory and lower temperature and pressure ranges available, various compositions of Ethane-Pentane system were studied in order to design the experimental parameters. The results of this study will be used by the rest of the members in the research team to conduct the experiments as it provided them with the most suitable system to explore in the laboratory.
Keywords: Phase behavior; EXPERIMENTAL PARAMETERS REQUIRED TO STUDY HYDROCARBON; CONSTANT VOLUME AND CONSTANT COMPOSITION CONDITIONS